Maternal health care services in Nepal: A qualitative perspective based on the socio-ecological model - Sharma, Mohan Kumar; Khanal, Shanti Prasad; Adhikari, Ramesh; Acharya, Jib (Journal of Health Promotion, 2021)
Nepal has a high Maternal Mortality Rates (MMR) in the South Asian region, partly due to the poor utilization of maternal and child healthcare services. The study aims to explore the influencing factors of maternal and child healthcare services among Nepalese women. Eighteen women, who had seven-days-old-children and those recently accessed maternal and child healthcare practices, were purposively selected. The face-to-face, In-depth-Interview (IDI) was applied to collect the information. The data were thematically analyzed, where Socio-Ecological Model (SEM) was applied as a theoretical framework. The study showed that the factors such as the knowledge of women, perception, and decision-making-autonomy at individual levels influenced maternal and child healthcare-seeking behaviors. Likewise, mothers-in-law and the role of husbands at intrapersonal levels, employment at institutional levels, peers and role of neighbors at community levels, and safe motherhood program at policy levels were significant factors for the utilization of maternal and child healthcare-seeking-behaviors. The negligence of women concerning pregnancy, inadequate health facilities, lack of specialist health workers with advanced equipment, and cultural taboos and beliefs were observed as score barriers for utilization of maternal and child health-seeking behaviors. The research strongly recommends that all women be aware of maternal and child healthcare and health-seeking behaviors at their initial ages.